ИЧКИ ИШЛАР ОРГАНЛАРИ ТИЗИМИДА ПСИХОЛОГИК ХИЗМАТ: МУАММО ВА ЕЧИМЛАР - Душанов, Р.Х. (SCIENCE and SOCIETY, 2024)
This article presents the problems and solutions of the psychological service in the system of internal affairs bodies, as well as the socio-psychological factors for their improvement.